TRADISI KEHAMILAN, PERSALINAN, DAN NIFAS MASYARAKAT BADUY SERTA DAMPAKNYA PADA KESEHATAN IBU: A SCOPING REVIEW - Nurlaili, Helmi (Jurnal Kebidanan, 2023)
The problems of reducing Maternal Mortality Rate (MMR) are geographical variations, lack of infrastructure, and cultural aspects. The Baduy community upholds their traditions by rejecting technology. They live in Kendeng mountain. Baduy region contributed the highest of Banten's MMR in 2022 with 6 cases. The researcher analyzed the traditions of pregnancy, childbirth, and postpartum of Baduy community. This scoping review study was conducted in Juni 2021 in the five databases. The scoping review stages include identifying research questions, searching for relevant research, selecting and choosing literature, extracting data, as well as compiling a synthesis and drawing conclusions. The article search used the keywords "Baduy AND health AND maternal OR mother AND pregnancy AND childbirth OR delivery AND postpartum". Baduy mothers check their pregnancy to paraji and get abdominal massage. They wear cutter (small knife) and needle amulet. Food restrictions are chili sauce, durian, petai, pineapple, hot cai, and peanuts. Childbirth takes place in home, without light, and not sterile. Mothers are forbidden to eating and drinking while waiting for the paraji. After that, they bath in the river and get abdominal massage. Postpartum blood is cleaned using cloth they worn. Mothers should not eat animal protein and use contraceptives. Some cultures have negative impact on mother. Health workers should educate the community continuously and always be ready if needed. Coordination between government and traditional leader is needed to monitor the road and bridges.